Modern approaches in endodontic treatment of irreversible pulpitis - S. L. Blashkova; J. V. Fazylova; E. V. Krikun; R. R. Fatihova (LLC "Endo Press", 2020)
Relevance. Currently, there are a large number of methods and instruments for the root canal system highquality biomechanical instrumental processing and subsequent obturation. In recent years, more and more scientific works in dentistry have focused on the fact that only 10% of root canals have no branches, and the classical canal has many additional canals. In this connection, the search for endodontic treatment methods that provide high-quality both the main and lateral canals obturation remains relevant. Aim was to increase the irreversible pulpitis treatment clinical effectiveness.  Materials and methods. We have carried out a comparative assessment of the root canals instrumental treatment effectiveness by reciprocation instrument followed by obturation using the vertical condensation technique in 15 patients with irreversible pulpitis. The comparison group consisted of 12 patients with chronic pulpitis, in the treatment of which the traditional machine rotary instruments technique of root canals and obturation using the lateral condensation method of gutta percha were used.Results. Showed that the modern technologies use based on reciprocal instrument rotation with subsequent root canal obturation by the gutta percha vertical condensation method, is clinically justified, as evidenced by the comparative assessment data.Conclusions. High technological effectiveness of the methods used in combination with low complication risks at the stage of instrumental processing and obturation provides the patient with maximum comfort in the postoperative period, as evidenced by the indicators of the verbal pain assessment scale, show minimal time spent on the procedure, which is important in the ergonomic work at the present stage . The endodontic treatment results of patients with the Reciproc and BeeFill systems use give reason to recommend their application in the dental practice.